Stormtime Energetics: Energy Transport Across the Magnetopause in a Global MHD Simulation - Brenner, Austin; Pulkkinen, Tuija I.; Al Shidi, Qusai; Toth, Gabor (Frontiers in Astronomy and Space Sciences, 2021)
Coupling between the solar wind and magnetosphere can be expressed in terms of energy transfer through the separating boundary known as the magnetopause. Geospace simulation is performed using the Space Weather Modeling Framework (SWMF) of a multi-ICME impact event on February 18-20, 2014 in order to study the energy transfer through the magnetopause during storm conditions. The magnetopause boundary is identified using a modified plasma β and fully closed field line criteria to a downstream distance of −20Re. Observations from Geotail, Themis, and Cluster are used as well as the Shue 1998 model to verify the simulation field data results and magnetopause boundary location. Once the boundary is identified, energy transfer is calculated in terms of total energy flux K, Poynting flux S, and hydrodynamic flux H. Surface motion effects are considered and the spatial distribution is explored in terms of dayside (X > 0), flank (X < 0), and tail cap (X = Xmin) regions. It is found that total integrated energy flux over the boundary is nearly balanced between injection and escape, and flank contributions dominate the Poynting flux injection. Poynting flux dominates net energy input, while hydrodynamic flux dominates energy output. Surface fluctuations contribute significantly to net energy transfer and comparison with the Shue model reveals varying levels of cylindrical asymmetry in the magnetopause flank throughout the event. Finally existing energy coupling proxies such as the Akasofu ε parameter and Newell coupling function are compared with the energy transfer results.